Contribution of Remittance to the National Economy of Federal Nepal (PAAN Journal, 2025)
Labour migration from their nation to another country for employment is called foreign employment. The trend of migration of human resources in Nepal has been prevalent throughout the ancient history of Nepal. In this study, the trend of foreign employment is analyzed using statistics like the labour approval based on the level of skill, labour approval received by the male and female, major destination country for labour approval, remittance received by the country in the fiscal year, national savings, disposable income, foreign exchange reserve of the nation, economic growth, Human Development Index and contribution of remittance on the national economy. Remittance is the second largest contribution to Nepal's national economy. Most of the migrant workers are unskilled in foreign land from Nepal. Professional and highly skilled workers are minimally from Nepal in foreign lands. Nepali youth are choosing foreign employment for the job opportunities and better livelihoods in developed countries. Remittance generation is the main source for the government of Nepal. Modern economists claim that foreign remittance is not sustainable and good for the national economy. They suggested generating employment, industry, and marketization in the motherland i.e. Nepal. But practically remittance is the second contribution to the GDP of Nepal. Similarly, foreign employment and remittance contributed so many ways to Nepal such as dollar exchange, foreign trade balance, knowledge achievement, skilled transfer, technology advancement and so on.